The Keuneunong Dating and Acehnese Society - Darmadi Johan (Journal of Aceh Studies, 2024)
The important part of Acehnese culture is Keuneunong, especially for the Aneuk Jamee community and the Acehnese people as a whole. This ancient practice, in which farming is the main social activity, is strongly correlated with the seasonal calendar. An important part of Keuneunong, which symbolizes the practice's cultural and environmental significance, is the yearly Khanduri Laot rite in lowland Aceh. The purpose of this essay is to examine the cultural and social ramifications of Keuneunong in Acehnese society, providing insight into its history, customs, and changing function.